Marketing Relacional para la Internacionalización en Instituciones de Educación Superior del Caribe colombiano (2017)
This research seeks to describe Relational Marketing as a fundamental element for the strengthening of Internationalization in Higher Education Institutions (HEIs) of the colombian Caribbean, supported by the theoretical approaches of Berry (1983), Kotler y Keller (2012), Burgos (2007), Renart y Cabré (2007), Salazar (2014), Gacel-Ávila (2000), Salmi (2014) and Sebastian (2005). Using a deductive epistemological approach, a quantitative paradigm and a non-experimental field design, the survey technique was used and through a questionnaire with a Likert scale, the heads of the International Relations Office of 26 Higher Education Institutions (HEI) in the colombian Caribbean. Their reliability was determined by the Alpha Cronbach coefficient (rtt = 0.939) which reflects consistency and balance in the instrument. The data were processed by means of descriptive statistics: summation, absolute and relative frequency; as well as measures of central tendency such as mean and standard deviation. The results obtained evidenced a medium level inclusion of phases and elements of Relational Marketing in the institutional activities, with a satisfactory tendency in the use of relational strategies. The HEIs also had greater strength in the Internationalization of Teaching, supported by student and teacher mobility, and in contrast there was evidence of weakness in the Internationalization of Extension, with a lack of headquarters outside the studied institutions